THE USE OF A SOFTWARE BUILT IN THE DELPHI PROGRAMMING ENVIRONMENT TO MIX TEST QUESTIONS WITH MULTI-ROW OBJECTS IN MICROSOFT WORD DOCUMENTS - Azizbek Mahkamov (European Science Publishing, 2024)
This article examines the issue of mixing test questions with multiple lines of objects in Microsoft Word documents and creating a test option. The advantages and disadvantages of transferring test questions involving multi-line objects to the test option using a program created in the Delphi programming environment are considered.
Keywords: Microsoft Word, Delphi, object-oriented text strings, General secondary school.